hepar image anatomical information, HU score, bolus tracking technique. - Siti Masrochah; Maria Ermelinda Teme; Luthfi Rusyadi (Jurnal Imejing Diagnostik (JImeD), 2015)
Background: The appropriate adjustment of HU score on bolus tracking image will give us the same time between duration of scan and duration of injecting contrast media. The optimal contrast enhancement will give the optimal information of anatomical and patological image of organ. This research aims to determine the quality of hepar image anatomy based on the variety of HU score and find out the optimal score that can provide anatomical information image of the liver.Methods: This research was a quantitative research with an experimental approach. Subjects of this study were five patients for every single variation of three HU scores variation (100 HU, 150 HU, and 200 HU). This study was conducted in dr. Kanudjoso Jatiwibowo Balikpapan Hospital on May to June 2016. The sample was taken by purposive sampling technique, because it was not done on whole of population but only focused on certain targets. Parameters used were flow rate, pressure, concentration of the contrast media and patient’s physiology . The assesment of the liver arterial phase was done by three radiology physician using checklist to determine the quality of hepar image anatomical information. Data analyzed by non-parametric statistical test of Kruskal-Wallis test with SPSS 16 version.Results: Quality of hepar anatomical information was based on the HU score variations. The statistical test score was 0.01 that means that Ho was rejected and Ha was accepted, significant differences between the quality of anatomical information of hepar image with the variety of HU score on tracking bolus technique.Conclusion: The optimal score which can provide better quality of hepar image anatomical information was on 200 HU.